Quantitative analyses of Mn, V, and Si elements in steels using a portable laser-induced breakdown spectroscopy system based on a fiber laser. Issue 3 (28th January 2016) - Zeng, Qingdong; Guo, Lianbo; Li, Xiangyou; Shen, Meng; Zhu, Yining; Li, Jiaming; Yang, Xinyan; Li, Kuohu; Duan, Jun; Zeng, Xiaoyan; Lu, Yongfeng
Abstract : An approach of portable laser-induced breakdown spectroscopy based on a fiber laser with a background removal method was proposed. Abstract : A portable laser-induced breakdown spectroscopy (LIBS) system based on a fiber laser was developed and employed to quantitatively analyze manganese (Mn), vanadium (V), and silicon (Si) elements in steels. After background removal, the coefficients of determination ( R 2 factors) of the calibration curves for Mn, V, and Si elements reached 0.997, 0.991 and 0.992, respectively, obvious improvements compared to those of the original spectra. The leave-one-out cross-validation (LOOCV) method was used to test the system. The root-mean-square error of cross-validation (RMSECV) for Mn (0.072–2.06 wt%), V (0.009–0.821 wt%), and Si (0.099–1.85 wt%) elements were 0.037, 0.041 and 0.079 wt%, respectively. The average relative errors (AREs) for Mn elements reached 7.6%. These results are comparable with those of the conventional LIBS which refers to utilizing the traditional flash-lamp-pumped laser as a laser source. However, compared to conventional LIBS, a fiber laser LIBS (FL-LIBS) is more compact, robust, and cost effective. The FL-LIBS, coupling a compact fiber laser and spectrometer, is a convenient approach to providing a portable solution for real-time and in situ detection in industry, especially in harsh environments.